Framing post-conflict societies: an analysis of the international pathologisation of Cambodia and the post-Yugoslav states - Hughes, Caroline; Pupavac, Vanessa (Taylor & Francis, 2005)
The article examines the pathologisation of post-conflict societies through a comparison of the framing of the Cambodian and post-Yugoslav states. The notion of failed states fixes culpability for war on societies in question, rendering the domestic populations dysfunational while casting international rescue interventions as functional. The article suggests that the discourse of pathologisation can be understood not as a means of explaining state crisis so much as legitimising an indefinite international presence and deferring self-government.